Herod Wielki i „nowa” Jerozolima - Maciudzińska-Kamczycka, Magdalena (Studia Europaea Gnesnensia, 2013)
The focus of this paper will be on the Jewish experience with Roman art in the late Second Temple period, from Herod’s reign ( 37-4 B.C.E.) to the destruction of the Jerusalem Temple in 70 C.E. Herodian architecture of Jerusalem, existing in the archaeological artefacts and the writings of ancient authors, is reflective of both full Jewish participation in Roman art and a level of local conservatism.